Fiscal Transfers, Institutional Quality, and the Moderation Paradox: Panel Evidence from Indonesian Local Governments - Muhammad Bagus Sistriatmaja; Yogi Pasca Pratama; Bhimo Rizky Samudro; Luthfi Sulthan Jauhary Lito; Mohammad Tawfik Bin Yakuub (Academic Bright Collaboration, 2026)
Purpose - This study investigates how regional institutional quality moderates the relationship between fiscal transfers and local government financial performance in Indonesia. Methods - The study uses panel data from 542 Indonesian local governments during 2015–2024. Fixed effects estimation, moderated regression analysis, IV-2SLS, and threshold regression are applied to test the transfer–performance relationship. Findings - Fiscal transfers significantly reduce fiscal autonomy, confirming the flypaper effect. Their effect on capital expenditure is mixed: fixed effects estimation shows a negative within-unit effect, while IV-2SLS indicates a positive causal estimate. The study identifies an institutional moderation paradox, where higher HDI strengthens the negative effect of transfers on fiscal autonomy. For capital expenditure, transfers have a positive effect at average HDI levels but become negative in the top 8% of regions. A preliminary transfer threshold of around 69% is identified, below which fiscal autonomy is more strongly weakened. Research implications - The findings suggest that institutional strengthening alone is insufficient to overcome fiscal dependency without reforming transfer incentives. The HKPD Law 2022 is associated with increased fiscal autonomy but reduced capital expenditure, requiring further causal investigation. Future studies should use direct governance indicators and formally validate the transfer threshold. Originality - This study provides an explicit moderation analysis across all Indonesian local governments over a decade. It contributes by documenting the institutional moderation paradox and identifying a preliminary fiscal transfer saturation point in Indonesia.